Four new species of the genus Pseudosubhimalus (Hemiptera: Cicadellidae) from the Indian subcontinent - Niranjana, G.n.; Meshram, Naresh M.; Stuti, Stuti; Sunil, Sunil; Nikoshe, Akash Prakash (Zootaxa, 2020)
Four new species of leafhoppers, Pseudosubhimalus asymmetricus sp. nov. (Himachal Pradesh: Katrain), P. dalangensis sp. nov. (Himachal Pradesh: Dalang), P. katraini sp. nov. (Himachal Pradesh: Katrain), P. lachungensis sp. nov. (Sikkim: Lachung), are described from the Indian subcontinent. A checklist and key to the species of Pseudosubhimalus are provided.